2011
DOI: 10.1099/vir.0.029322-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a neutralizing epitope in the surface envelope protein of porcine endogenous retrovirus subgroup B

Abstract: Pigs are thought to be the most suitable donor animal for xenotransplantation. However, pigs harbour potentially hazardous infectious agents, termed porcine endogenous retroviruses (PERVs), in their genome. In this study, we generated a mAb against PERV-B surface (SU) envelope protein (Env), designated KRT1. KRT1 binding was detected by an indirect immunofluorescence assay and flow cytometric analysis on cells infected with PERV-B. KRT1 neutralized PERV-B pseudotype virus and specifically recognized PERV-B SU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…More recent developments in this field include new monoclonal antibodies with neutralizing activity. Nakaya, et al, have described a monoclonal antibody that potently neutralizes PERV-B, but not PERV-A (Nakaya, Hoshino et al 2011). Interestingly, the epitope for this neutralizing antibody maps to the proline-rich region, a finding that corresponds to previously described observations that correlate human cell infection with determinants within the PRR (see section 2.2.3).…”
Section: Strategies To Prevent or Treat Perv Infection In Humanssupporting
confidence: 61%
See 1 more Smart Citation
“…More recent developments in this field include new monoclonal antibodies with neutralizing activity. Nakaya, et al, have described a monoclonal antibody that potently neutralizes PERV-B, but not PERV-A (Nakaya, Hoshino et al 2011). Interestingly, the epitope for this neutralizing antibody maps to the proline-rich region, a finding that corresponds to previously described observations that correlate human cell infection with determinants within the PRR (see section 2.2.3).…”
Section: Strategies To Prevent or Treat Perv Infection In Humanssupporting
confidence: 61%
“…A monoclonal antibody specific to the PERV gag protien was shown useful for detecting infection (Chiang, Chang et al 2005) . Recently, a monoclonal antibody directed against the PERV-B envelope protein detected a specific peptide sequence in the proline rich region of SU as an epitope for PERV infection (Nakaya, Hoshino et al 2011) . These monoclonal antibodies may prove useful for screening for PERV antigen, although to date no xenotransplantation studies have used the antibody on porcine or human xenotransplant recipient samples.…”
Section: Immunoassaymentioning
confidence: 99%
“…Of note, insertion of tags tolerated in other gammaretroviruses into the PERV PRR renders vectors carrying the tagged envelopes noninfectious (C. Wilson, data not shown), further supporting the distinct structural impact of the PRR on envelope function. Recently, it was reported that a neutralizing antibody to PERV-B recognizes a peptide within the PRR (15), suggesting that the region is exposed to antibodies. Interestingly, the particular epitope identified is absent from both PERV-A and PERV-C (15).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that a neutralizing antibody to PERV-B recognizes a peptide within the PRR (15), suggesting that the region is exposed to antibodies. Interestingly, the particular epitope identified is absent from both PERV-A and PERV-C (15).…”
Section: Discussionmentioning
confidence: 99%
“…IFA was applied as previously described, with slight modifications (26). Briefly, cells transfected with indicated plasmids were fixed with 4% PFA on ice for 30 min, followed by blocking in blocking buffer at room temperature (RT) for 1 h, reaction with anti-FLAG M2 diluted at 1:500 in antibody dilution buffer (PBS containing 1% BSA) at RT for 2 h, staining with anti-mouse IgG conjugated with Alexa Fluor 594 (Invitrogen) diluted at 1:1,500 in antibody dilution buffer at RT for 1 h, and staining with 1 ng/ml 4=,6-diamidino-2-phenylindole (DAPI) solution at RT for 5 min.…”
Section: Methodsmentioning
confidence: 99%